# 0.9k-0.3(k+0.6)=0.2(k+0.1)

## Simple and best practice solution for 0.9k-0.3(k+0.6)=0.2(k+0.1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 0.9k-0.3(k+0.6)=0.2(k+0.1) equation:

0.9k-0.3(k+0.6)=0.2(k+0.1)
We move all terms to the left:
0.9k-0.3(k+0.6)-(0.2(k+0.1))=0
We multiply parentheses
0.9k-0.3k-(0.2(k+0.1))-0.18=0

We calculate terms in parentheses: -(0.2(k+0.1)), so:
0.2(k+0.1)
We multiply parentheses
0.2k+0.02
Back to the equation:
-(0.2k+0.02)

We add all the numbers together, and all the variables
0.6k-(0.2k+0.02)-0.18=0
We get rid of parentheses
0.6k-0.2k-0.02-0.18=0
We add all the numbers together, and all the variables
0.4k-0.2=0
We move all terms containing k to the left, all other terms to the right
0.4k=0.2
k=0.2/0.4
k=0.2/0.4

`